Thermal fabric containing hollow polyester fibers as well as preparation method and application of thermal fabric

By using modified hollow mesoporous nano cerium oxide and polyethylene glycol 10000 in warm fabrics, combined with melt spinning and chemical treatment technology, hollow polyester fiber warm fabrics with excellent anti-static properties and flame retardant properties are prepared, solving the problems of static electricity and flammability of existing fabrics in cold environments.

CN119640589AInactive Publication Date: 2025-03-18SHANTOU XINMAOFENG TEXTILE IND CO LTD
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202510174691.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-18
Publication Date
2025-03-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing warm fabrics are prone to static electricity in cold environments, affecting health and safety, and the moisture rebate rate of polymer materials is low, resulting in flammable materials.

Method used

The warm fabric containing hollow polyester fiber is used. The preparation method includes mixing modified polyester granules, modified hollow mesoporous nano cerium oxide and polyethylene glycol 10000 and melt-spinning, and then treating it with pyrrole solution and sodium hypochlorite mixed solution to form a fabric with excellent antistatic properties and flame retardant properties.

Benefits of technology

Improves the antistatic, flame retardant and warmth of the fabric, reduces the risk of static electricity and combustion, and enhances the safety and performance of the fabric.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_5
    Figure SMS_5
  • Figure SMS_6
    Figure SMS_6
Patent Text Reader

Abstract

The invention discloses a warm-keeping fabric containing hollow polyester fibers as well as a preparation method and application thereof, and relates to the field of fabrics. When the thermal fabric containing the hollow polyester fibers is prepared, hollow mesoporous nano cerium oxide is selectively protected by molten paraffin and then reacts with chloromethyl trimethoxy silane and isocyanuric acid in sequence, paraffin is dissolved by chloroform, and then N-(3-trimethoxysilylpropyl) pyrrole is grafted to obtain modified hollow mesoporous nano cerium oxide; reacting terephthalic acid, a multifunctional monomer and ethylene glycol to obtain modified polyester particles; the preparation method comprises the following steps: granulating modified polyester, uniformly mixing modified hollow mesoporous nano cerium oxide and polyethylene glycol 10000, performing melt spinning, treating with a pyrrole solution, twisting, spinning and weaving, and treating with a sodium hypochlorite mixed solution to obtain the thermal fabric containing the hollow polyester fibers. The warm-keeping fabric containing the hollow polyester fibers prepared by the invention has excellent warm-keeping, antibacterial, anti-aging, flame-retardant, antistatic and mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of fabrics, in particular to a thermal insulation fabric containing hollow polyester fibers and a preparation method and application thereof. Background Art

[0002] When the human body is in a cold environment, the amount of heat dissipated by the body will increase dramatically. When the heat generated by the body's own temperature regulation system is difficult to maintain the normal body temperature, it will cause a series of physiological and even pathological changes. When people are in cold conditions, they often have physical reactions such as shivering. When people are in an extremely cold environment for a long time, it will cause great damage to the human body and even endanger people's lives.

[0003] With the development of social industrial level and increasingly severe global climate change, people have put forward higher requirements on the thermal insulation performance of thermal insulation materials. In order to further improve the thermal insulation performance, we need to prepare fiber thermal insulation materials with better thermal insulation performance, and the preparation methods include composite spinning method, melt-blown spinning method, electrostatic spinning method and flash evaporation method. However, due to the low moisture regain of the polymer material used, the prepared thermal insulation material is prone to static electricity, which seriously affects people's health and life, and even causes fires in some special environments, posing great safety hazards. Therefore, the present invention prepares a thermal insulation fabric containing hollow polyester fibers with excellent antistatic properties. Summary of the invention

[0004] The purpose of the present invention is to provide a thermal insulation fabric containing hollow polyester fibers and a preparation method and application thereof, so as to solve the problems existing in the prior art.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: a thermal insulation fabric containing hollow polyester fibers, wherein the thermal insulation fabric containing hollow polyester fibers is prepared by mixing modified polyester pellets, modified hollow mesoporous nano-cerium oxide and polyethylene glycol 10000, melt-spinning the mixture, treating the mixture with a pyrrole solution, twisting and spinning the mixture, and then treating the mixture with a sodium hypochlorite mixture.

[0006] As an optimization, the polyethylene glycol 10000 comes from Shandong Baihua Chemical Co., Ltd.

[0007] As an optimization, the modified polyester pellets are obtained by reacting 5-(1H-pyrrol-1-yl)-2-mercaptobenzimidazole with dimethyl chlorophosphate, and then reacting with terephthalic acid and ethylene glycol.

[0008] As an optimization, the hollow mesoporous nano-cerium oxide is selectively protected by melted paraffin and then reacted with chloromethyltrimethoxysilane and isocyanuric acid in sequence, and then the paraffin is dissolved by chloroform and then grafted with N-(3-trimethoxysilylpropyl)pyrrole to obtain it.

[0009] As an optimization, the hollow mesoporous nano-cerium oxide model is 100 nm and comes from Nanjing Jike Biotechnology Co., Ltd.

[0010] A method for preparing a thermal insulation fabric containing hollow polyester fibers, comprising the following preparation steps: (1) Mix the hollow mesoporous nano-cerium oxide, hexadecyltrimethylammonium chloride and deionized water in a mass ratio of 1: (0.02-0.03): (85-95), ultrasonicate for 25-35 min, add 9-11 times the mass of the hollow mesoporous nano-cerium oxide melted paraffin, stir at 65-75 ° C and 7000-8000 rpm for 5-15 min, let stand and cool to room temperature, filter, wash with anhydrous ethanol and deionized water for 3-5 times respectively, dry at 50-60 ° C for 11-13 h, grind and sieve 200-300 mesh , obtain semi-protected hollow mesoporous nano-cerium oxide; mix the semi-protected hollow mesoporous nano-cerium oxide, chloromethyltrimethoxysilane and 97%~98% ethanol aqueous solution in a mass ratio of 1: (1.7~1.9): (150~250), ultrasonically disperse for 25~35min, heat to 55~65℃, stir at 200~300rpm for 2~4h, cool naturally to room temperature and centrifuge, wash with anhydrous ethanol for 3~5 times, dry at 45~55℃ for 47~49h, and obtain pre-modified hollow mesoporous nano-cerium oxide; (2) Pre-modified hollow mesoporous nano-cerium oxide, isocyanuric acid, sodium hydroxide and deionized water are mixed in a mass ratio of 1: (2-3): (1-2): (90-110), stirred at 20-30°C and 300-400 rpm for 11-13 h, added with 50%-60% sulfuric acid solution to adjust the pH to 5-7, allowed to stand for 1-2 h and then filtered, washed with deionized water for 3-5 times to obtain semi-modified hollow mesoporous nano-cerium oxide; semi-modified hollow mesoporous nano-cerium oxide and chloroform are mixed in a mass ratio of 1: (9-11), stirred at 20-30°C and 100-200 rpm for 85- After 95 minutes, filter, wash with chloroform, anhydrous ethanol and deionized water for 3 to 5 times, and dry at 35 to 45°C for 23 to 25 hours to obtain semi-modified hollow mesoporous nano-cerium oxide; mix the semi-modified hollow mesoporous nano-cerium oxide, N-(3-trimethoxysilylpropyl)pyrrole and anhydrous ethanol in a mass ratio of 1: (0.2 to 0.3): (45 to 55), stir at 45 to 55°C and 200 to 300 rpm for 3 to 5 hours, cool naturally to room temperature and then filter, wash with anhydrous ethanol and deionized water for 3 to 5 times, and dry at 35 to 45°C for 23 to 25 hours to obtain modified hollow mesoporous nano-cerium oxide; (3) 5-(1H-pyrrol-1-yl)-2-mercaptobenzimidazole, triethylamine and tetrahydrofuran were mixed in a mass ratio of 1: (0.5-0.7): (10-12), stirred at 200-400 rpm for 10-20 min in a nitrogen atmosphere, and 0.6-0.7 times the mass of 5-(1H-pyrrol-1-yl)-2-mercaptobenzimidazole dimethyl chlorophosphate was added dropwise at 0-5°C, the temperature was raised to 45-55°C, and stirring was continued for 5-7 h. Ethyl acetate was added for extraction, and the organic phase was dried over anhydrous sodium sulfate and filtered, rotary evaporated, and separated and purified with petroleum ether ethyl acetate eluent to obtain a multifunctional monomer; (4) Terephthalic acid, multifunctional monomer, ethylene glycol and ethylene glycol antimony are mixed in a mass ratio of 1: (0.8-0.9): (0.6-0.7): (0.01-0.03), heated at 140-150°C for 20-30 min, heated to 175-185°C, stirred at 75-85 rpm for 1-3 h, heated to 240-260°C for vacuum reaction for 20-30 min, cooled naturally to room temperature, taken out and pelletized to obtain modified polyester pellets; modified polyester pellets, modified hollow mesoporous nano-cerium oxide and polyethylene glycol 10000 are mixed in a mass ratio of 1: (0.02-0.04): (0.01-0.02), and spun by a twin-screw spinning machine. A spinning machine is provided, wherein nitrogen is introduced as a core liquid, and melt spinning is performed under the conditions of 1300-1500 spinneret holes, 2-4 cm height of a windless zone, 1200-1400 m / min, 110-120 m / min, melt receiving amount 450-550 kg / h, total stretching multiple of post-spinning 3.5-3.7, first stretching ratio 3.25-3.27, second stretching ratio 1.06-1.08, spinning temperature 287-289° C., blowing temperature 20-22° C., and blowing humidity 65%-75% RH, and the melt is cooled and solidified in air, washed with deionized water 3-5 times, and dried at 20-30° C. for 23-25 ​​hours to obtain spun fibers; (5) Immerse the spun fiber in a 0.1-0.3 mol / L pyrrole solution, perform ultrasonic treatment for 15-25 min, add a 0.3-0.5 mol / L ferric chloride solution, wherein the molar ratio of ferric chloride to pyrrole is 3:1, perform ultrasonic treatment at 0-5°C for 55-65 min, take out the fiber, wash it with deionized water for 3-5 times, dry it at 55-65°C for 8-10 h, and obtain a modified fiber; mix the modified fiber and wool fiber at a mass ratio of 1:1, blend them on a B412 blending machine, and then perform first needle, second needle, combing, and combing on a CSN gill combing machine. The yarn was combed with three needles, stretched and twisted on a FB441 roving frame, stretched and twisted on a SHS24 spinning frame to obtain a blended yarn; the blended yarn was woven on a machine with a 2 / 1 right-hand twill weave at a fabric tightness of 97.33% to obtain a fabric to be treated; the fabric to be treated and a sodium hypochlorite mixed solution were mixed at a mass ratio of 1: (25-35), immersed at 20-30°C for 55-65min, washed with deionized water for 3-5 times after being taken out, and dried at 40-50°C for 1-3h to obtain a warm fabric containing hollow polyester fibers.

[0011] As an optimization, the melted paraffin in step (1) is obtained by heating the sliced ​​paraffin at 70°C until it melts.

[0012] As an optimization, the slice paraffin comes from Hubei Xinjiecheng Chemical Technology Co., Ltd.

[0013] As an optimization, the equation of the semi-protected hollow mesoporous nano-cerium oxide in step (1) is: .

[0014] As an optimization, the reaction equation for modifying the hollow mesoporous nano-cerium oxide in step (2) is: .

[0015] As an optimization, the petroleum ether ethyl acetate eluent in step (3) is obtained by mixing petroleum ether and ethyl acetate in a volume ratio of 12:1.

[0016] As an optimization, the reaction equation of the multifunctional monomer in step (3) is: .

[0017] As an optimization, the reaction equation for the modified polyester pelletizing in step (4) is: .

[0018] As an optimization, the blended spinning parameters in step (5) are: single yarn count 73 / 1, twist 780 twists / m, twist direction Z; ply yarn 72 / 2, twist 800 twists / m, twist direction S.

[0019] As an optimization, the sodium hypochlorite mixed solution in step (5) is obtained by mixing sodium hypochlorite solution and deionized water in a volume ratio of 1:10, and adding a 60% by mass sulfuric acid solution to adjust the pH to 7.

[0020] As an optimization, the sodium hypochlorite solution comes from Guangdong Xiaoda Chemical Co., Ltd.

[0021] The invention discloses an application of a thermal insulation fabric containing hollow polyester fibers in textiles.

[0022] Compared with the prior art, the beneficial effects achieved by the present invention are as follows: when preparing a thermal insulation fabric containing hollow polyester fiber, the present invention selectively protects the hollow mesoporous nano cerium oxide with melted paraffin and then reacts with chloromethyltrimethoxysilane and isocyanuric acid in sequence to obtain a semi-modified hollow mesoporous nano cerium oxide; then the semi-modified hollow mesoporous nano cerium oxide is dissolved in paraffin with chloroform and then grafted with N-(3-trimethoxysilylpropyl)pyrrole to obtain a modified hollow mesoporous nano cerium oxide; 5-( The invention relates to a method for preparing a thermal insulation fabric containing hollow polyester fibers, wherein the modified polyester fibers are prepared by reacting terephthalic acid, the multifunctional monomer and ethylene glycol to obtain a modified polyester pellet; the modified polyester pellet, the modified hollow mesoporous nano-cerium oxide and polyethylene glycol 10000 are mixed and melt-spun, and then treated with a pyrrole solution to obtain a modified fiber; the modified fiber is twisted and spun and then woven, and then treated with a sodium hypochlorite mixed solution to obtain a thermal insulation fabric containing hollow polyester fibers.

[0023] Firstly, hollow mesoporous nano-cerium oxide is selectively protected by melted paraffin and then reacted with chloromethyltrimethoxysilane and isocyanuric acid in sequence to obtain semi-modified hollow mesoporous nano-cerium oxide; then, the semi-modified hollow mesoporous nano-cerium oxide is dissolved in paraffin by chloroform and then grafted with N-(3-trimethoxysilylpropyl)pyrrole to obtain modified hollow mesoporous nano-cerium oxide; hollow mesoporous nano-cerium oxide is used as a reinforcing phase, and the hollow structure can effectively reduce heat conduction and improve the warmth retention of thermal insulation fabrics containing hollow polyester fibers; hollow mesoporous nano-cerium oxide is selectively protected by paraffin as an oil phase, and isocyanuric acid is grafted on the surface of the hollow mesoporous nano-cerium oxide. A halamine precursor is formed, and after reacting with sodium hypochlorite, a halamine structure is obtained that can destroy or prevent the normal metabolism of cells and promote the death of bacteria, thereby improving the antibacterial property of thermal insulation fabrics containing hollow polyester fibers. By utilizing the characteristics that paraffin is soluble in chloroform but insoluble in ethanol and deionized water, N-(3-trimethoxysilylpropyl)pyrrole is grafted on the other surface of the hollow mesoporous nano-cerium oxide to form a polypyrrole long chain with the polyester main chain, thereby improving the mechanical properties of the thermal insulation fabrics containing hollow polyester fibers. At the same time, the conjugated chain structure of the polypyrrole long chain has good electron transmission ability, thereby further improving the antistatic property of the thermal insulation fabrics containing hollow polyester fibers.

[0024] Secondly, 5-(1H-pyrrole-1-yl)-2-mercaptobenzimidazole and dimethyl chlorophosphate are reacted to obtain a multifunctional monomer; terephthalic acid, the multifunctional monomer and ethylene glycol are reacted to obtain modified polyester pellets; the modified polyester pellets, modified hollow mesoporous nano-cerium oxide and polyethylene glycol 10000 are mixed and melt-spun, and then treated with a pyrrole solution to obtain modified fibers; the modified fibers are twisted and spun and then woven, and then treated with a sodium hypochlorite mixture to obtain a thermal insulation fabric containing hollow polyester fibers; a multifunctional monomer with phosphorus and benzene ring conjugated groups is synthesized by substitution reaction of mercapto and acyl chloride, and participates in the polymerization of the polyester main chain. The phosphorus element can inhibit the generation of free radicals, promote the formation of a carbonized protective layer, and slow down the rate of the combustion reaction during the propagation of the flame. , improving the flame retardant properties of thermal insulation fabrics containing hollow polyester fibers; the conjugated rings in 5-(1H-pyrrole-1-yl)-2-mercaptobenzimidazole can absorb ultraviolet rays, improving the anti-aging properties of thermal insulation fabrics containing hollow polyester fibers; using polyethylene glycol 10000 as a porogen, it is convenient for pyrrole to polymerize between modified polyester pellets and modified hollow mesoporous nanocerium oxide to form long chains, construct a cross-linked network, and further improve the mechanical properties and antistatic properties of thermal insulation fabrics containing hollow polyester fibers; wool fibers are selected to be blended with hollow polyester fibers, and the curled shape of the wool fibers forms many tiny gaps that can store a large amount of air, thereby effectively blocking the invasion of external cold air and further improving the warmth retention of thermal insulation fabrics made of hollow polyester fibers. DETAILED DESCRIPTION

[0025] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0026] The raw materials used in the following examples and comparative examples are all commercially available: the polyethylene glycol 10000 is from Shandong Baihua Chemical Co., Ltd.; the hollow mesoporous nano-cerium oxide model is 100 nm, from Nanjing Jike Biotechnology Co., Ltd.; the sliced ​​paraffin is from Hubei Xinjiecheng Chemical Technology Co., Ltd.; the sodium hypochlorite solution is from Guangdong Xiaoda Chemical Co., Ltd.

[0027] Example 1 A method for preparing a thermal insulation fabric containing hollow polyester fibers, the method comprising the following preparation steps: (1) Hollow mesoporous nano-cerium oxide, hexadecyltrimethylammonium chloride and deionized water were mixed in a mass ratio of 1:0.02:85, ultrasonicated for 25 minutes, and melted paraffin wax 9 times the mass of the hollow mesoporous nano-cerium oxide was added, stirred at 65°C and 7000rpm for 15 minutes, allowed to stand and cool to room temperature, filtered, washed with anhydrous ethanol and deionized water for 3 times, dried at 50°C for 13 hours, ground and sieved through 200 mesh to obtain semi-protected hollow mesoporous nano-cerium oxide; semi-protected hollow mesoporous nano-cerium oxide, chloromethyltrimethoxysilane and 97% ethanol aqueous solution were mixed in a mass ratio of 1:1.7:150, ultrasonically dispersed for 25 minutes, heated to 55°C and stirred at 200rpm for 4 hours, naturally cooled to room temperature and centrifuged, washed with anhydrous ethanol for 3 times, and dried at 45°C for 49 hours to obtain pre-modified hollow mesoporous nano-cerium oxide; (2) Pre-modified hollow mesoporous nano-cerium oxide, isocyanuric acid, sodium hydroxide and deionized water were mixed in a mass ratio of 1:2:1:90, stirred at 20°C and 300 rpm for 13 h, 50% sulfuric acid solution was added to adjust the pH to 5, the mixture was allowed to stand for 1 h and then filtered, and washed with deionized water for 3 times to obtain semi-modified hollow mesoporous nano-cerium oxide; semi-modified hollow mesoporous nano-cerium oxide and chloroform were mixed in a mass ratio of 1:9, stirred at 20°C and 100 rpm for 95 min, and then filtered. Filter, wash with chloroform, anhydrous ethanol and deionized water for 3 times, and dry at 35°C for 25 hours to obtain semi-modified hollow mesoporous nano-cerium oxide; mix the semi-modified hollow mesoporous nano-cerium oxide, N-(3-trimethoxysilylpropyl)pyrrole and anhydrous ethanol in a mass ratio of 1:0.2:45, stir at 45°C and 200rpm for 5 hours, cool naturally to room temperature and then filter, wash with anhydrous ethanol and deionized water for 3 times, and dry at 35°C for 25 hours to obtain modified hollow mesoporous nano-cerium oxide; (3) 5-(1H-pyrrol-1-yl)-2-mercaptobenzimidazole, triethylamine and tetrahydrofuran were mixed in a mass ratio of 1:0.5:10, stirred at 200 rpm for 10 min in a nitrogen atmosphere, and dimethyl chlorophosphate (0.6 times the mass of 5-(1H-pyrrol-1-yl)-2-mercaptobenzimidazole) was added dropwise at 0°C, the temperature was raised to 45°C and stirring was continued for 7 h, ethyl acetate was added for extraction, the organic phase was dried over anhydrous sodium sulfate and filtered, rotary evaporated, and separated and purified with petroleum ether ethyl acetate eluent to obtain a multifunctional monomer; (4) Terephthalic acid, multifunctional monomer, ethylene glycol and ethylene glycol antimony were mixed in a mass ratio of 1:0.8:0.6:0.01, heated at 140°C for 30 min, heated to 175°C, stirred at 75 rpm for 3 h, heated to 240°C for vacuum reaction for 30 min, naturally cooled to room temperature, and pelletized to obtain modified polyester pellets; modified polyester pellets, modified hollow mesoporous nano-cerium oxide and polyethylene glycol 10000 were mixed in a mass ratio of 1:0.02:0.01 and spun using a twin-screw spinning machine. , nitrogen was introduced as the core liquid, melt spinning was carried out under the conditions of 1300 spinneret holes, 2 cm windless zone height, 1200 m / min, 110 m / min, melt receiving amount 450 kg / h, total stretching ratio of 3.5, first stretching ratio 3.25, second stretching ratio 1.06, spinning temperature 287°C, blowing temperature 20°C, blowing humidity 65% ​​RH, cooling and solidification in air, washing 3 times with deionized water, and drying at 20°C for 25 h to obtain spun fibers; (5) The spun fiber was immersed in a 0.1 mol / L pyrrole solution, ultrasonicated for 15 min, and then a 0.3 mol / L ferric chloride solution was added, wherein the molar ratio of ferric chloride to pyrrole was 3:1. After ultrasonicating at 0°C for 65 min, the fiber was taken out, washed with deionized water for 3 times, and dried at 55°C for 10 h to obtain a modified fiber. The modified fiber and wool fiber were mixed at a mass ratio of 1:1, blended on a B412 blending machine, and then combed on a CSN needle combing machine using the first needle, second needle, combing, and third needle. The yarn was carded, stretched and twisted on a FB441 roving frame, stretched and twisted on a SHS24 spinning frame to obtain a blended yarn; the blended yarn was woven on a machine with a 2 / 1 right-hand twill weave at a fabric tightness of 97.33% to obtain a treated fabric; the treated fabric and a mixed solution of sodium hypochlorite were mixed at a mass ratio of 1:25, immersed at 20°C for 65min, taken out and washed 3 times with deionized water, and dried at 40°C for 3h to obtain a warm fabric containing hollow polyester fibers.

[0028] Example 2 A method for preparing a thermal insulation fabric containing hollow polyester fibers, the method comprising the following preparation steps: (1) Hollow mesoporous nano-cerium oxide, hexadecyltrimethylammonium chloride and deionized water were mixed in a mass ratio of 1:0.025:90, ultrasonicated for 30 minutes, melted paraffin 10 times the mass of the hollow mesoporous nano-cerium oxide was added, stirred at 70°C and 7500rpm for 10 minutes, allowed to stand and cool to room temperature, filtered, washed with anhydrous ethanol and deionized water for 4 times respectively, dried at 55°C for 12 hours, ground and sieved through 250 mesh to obtain semi-protected hollow mesoporous nano-cerium oxide; semi-protected hollow mesoporous nano-cerium oxide, chloromethyltrimethoxysilane and 97.5% ethanol aqueous solution were mixed in a mass ratio of 1:1.8:200, ultrasonically dispersed for 30 minutes, heated to 60°C and stirred at 250rpm for 3 hours, naturally cooled to room temperature and centrifuged, washed with anhydrous ethanol for 4 times, dried at 50°C for 48 hours, and pre-modified hollow mesoporous nano-cerium oxide was obtained; (2) Pre-modified hollow mesoporous nano-cerium oxide, isocyanuric acid, sodium hydroxide and deionized water were mixed in a mass ratio of 1:2.5:1.5:100, stirred at 25°C and 350 rpm for 12 h, and a 55% mass fraction sulfuric acid solution was added to adjust the pH to 6. After standing for 1.5 h, the mixture was filtered and washed with deionized water for 4 times to obtain semi-modified hollow mesoporous nano-cerium oxide. Semi-modified hollow mesoporous nano-cerium oxide and chloroform were mixed in a mass ratio of 1:10, stirred at 25°C and 150 rpm for 90 m in, filtered, washed with chloroform, anhydrous ethanol and deionized water for 4 times, dried at 40°C for 24h, and obtained semi-modified hollow mesoporous nano-cerium oxide; semi-modified hollow mesoporous nano-cerium oxide, N-(3-trimethoxysilylpropyl)pyrrole and anhydrous ethanol were mixed in a mass ratio of 1:0.25:50, stirred at 50°C and 250rpm for 4h, naturally cooled to room temperature and filtered, washed with anhydrous ethanol and deionized water for 4 times, and dried at 40°C for 24h to obtain modified hollow mesoporous nano-cerium oxide; (3) 5-(1H-pyrrol-1-yl)-2-mercaptobenzimidazole, triethylamine and tetrahydrofuran were mixed in a mass ratio of 1:0.6:11, stirred at 300 rpm for 15 min in a nitrogen atmosphere, and dimethyl chlorophosphate (0.65 times the mass of 5-(1H-pyrrol-1-yl)-2-mercaptobenzimidazole) was added dropwise at 2.5°C. The temperature was raised to 50°C and stirred for 6 h. Ethyl acetate was added for extraction. The organic phase was dried over anhydrous sodium sulfate and filtered, rotary evaporated, and separated and purified with petroleum ether ethyl acetate eluent to obtain a multifunctional monomer. (4) Terephthalic acid, multifunctional monomer, ethylene glycol and ethylene glycol antimony were mixed in a mass ratio of 1:0.85:0.65:0.02, heated at 145°C for 25 min, heated to 180°C, stirred at 80 rpm for 2 h, heated to 250°C for vacuum reaction for 25 min, cooled naturally to room temperature, and pelletized to obtain modified polyester pellets; modified polyester pellets, modified hollow mesoporous nano-cerium oxide and polyethylene glycol 10000 were mixed in a mass ratio of 1:0.03:0.015, and spun by a twin-screw spinning machine. A spinning machine was used, nitrogen was introduced as the core liquid, and melt spinning was performed under the conditions of 1400 spinneret holes, 3 cm windless zone height, 1300 m / min, 115 m / min, melt receiving amount, 500 kg / h, total stretching ratio of 3.6, first stretching ratio, 3.26, second stretching ratio, 1.07, spinning temperature, 288°C, blowing temperature, 21°C, and blowing humidity, 70% RH, and the fibers were cooled and solidified in the air, washed with deionized water for 4 times, and dried at 25°C for 24 hours to obtain spun fibers; (5) The spun fiber was immersed in a 0.2 mol / L pyrrole solution, ultrasonicated for 20 min, and then a 0.4 mol / L ferric chloride solution was added, wherein the molar ratio of ferric chloride to pyrrole was 3:1. After ultrasonicating at 2.5°C for 60 min, the fiber was taken out, washed with deionized water for 4 times, and dried at 60°C for 9 h to obtain a modified fiber. The modified fiber and wool fiber were mixed at a mass ratio of 1:1, blended on a B412 blending machine, and then combed on a CSN needle combing machine using the first needle, second needle, combing, and third needle. The yarn was carded, stretched and twisted on a FB441 roving frame, stretched and twisted on a SHS24 spinning frame to obtain a blended yarn; the blended yarn was woven on a machine with a 2 / 1 right-hand twill weave at a fabric tightness of 97.33% to obtain a treated fabric; the treated fabric and a sodium hypochlorite mixture were mixed at a mass ratio of 1:30, immersed at 25°C for 60 minutes, taken out and washed with deionized water for 4 times, and dried at 45°C for 2 hours to obtain a warm fabric containing hollow polyester fibers.

[0029] Example 3 A method for preparing a thermal insulation fabric containing hollow polyester fibers, the method comprising the following preparation steps: (1) Hollow mesoporous nano-cerium oxide, hexadecyltrimethylammonium chloride and deionized water were mixed in a mass ratio of 1:0.03:95, ultrasonically dispersed for 35 minutes, and melted paraffin 11 times the mass of the hollow mesoporous nano-cerium oxide was added, stirred at 75°C and 8000rpm for 5 minutes, allowed to stand and cool to room temperature, filtered, washed with anhydrous ethanol and deionized water for 5 times respectively, dried at 60°C for 11 hours, ground and sieved through 300 mesh to obtain semi-protected hollow mesoporous nano-cerium oxide; semi-protected hollow mesoporous nano-cerium oxide, chloromethyltrimethoxysilane and 98% ethanol aqueous solution were mixed in a mass ratio of 1:1.9:250, ultrasonically dispersed for 25 minutes, heated to 65°C and stirred at 300rpm for 2 hours, naturally cooled to room temperature and centrifuged, washed with anhydrous ethanol for 5 times, and dried at 55°C for 47 hours to obtain pre-modified hollow mesoporous nano-cerium oxide; (2) Pre-modified hollow mesoporous nano-cerium oxide, isocyanuric acid, sodium hydroxide and deionized water were mixed in a mass ratio of 1:3:2:110, stirred at 30°C and 400 rpm for 11 h, and a 60% sulfuric acid solution was added to adjust the pH to 7. After standing for 2 h, the mixture was filtered and washed with deionized water for 5 times to obtain semi-modified hollow mesoporous nano-cerium oxide. Semi-modified hollow mesoporous nano-cerium oxide and chloroform were mixed in a mass ratio of 1:11, stirred at 30°C and 200 rpm for 85 min, and then the mixture was stirred for 10 min. Filter, wash with chloroform, anhydrous ethanol and deionized water for 5 times respectively, and dry at 45°C for 23 hours to obtain semi-modified hollow mesoporous nano-cerium oxide; mix the semi-modified hollow mesoporous nano-cerium oxide, N-(3-trimethoxysilylpropyl)pyrrole and anhydrous ethanol in a mass ratio of 1:0.3:55, stir at 55°C and 300rpm for 3 hours, cool naturally to room temperature and then filter, wash with anhydrous ethanol and deionized water for 5 times respectively, and dry at 45°C for 23 hours to obtain modified hollow mesoporous nano-cerium oxide; (3) 5-(1H-pyrrol-1-yl)-2-mercaptobenzimidazole, triethylamine and tetrahydrofuran were mixed in a mass ratio of 1:0.7:12, stirred at 400 rpm for 10 min in a nitrogen atmosphere, and dimethyl chlorophosphate (0.7 times the mass of 5-(1H-pyrrol-1-yl)-2-mercaptobenzimidazole) was added dropwise at 5°C, the temperature was raised to 55°C and stirring was continued for 5 h, ethyl acetate was added for extraction, the organic phase was dried over anhydrous sodium sulfate and filtered, rotary evaporated, and separated and purified with petroleum ether ethyl acetate eluent to obtain a multifunctional monomer; (4) Terephthalic acid, multifunctional monomer, ethylene glycol and ethylene glycol antimony were mixed in a mass ratio of 1:0.9:0.7:0.03, heated at 150°C for 20 min, heated to 185°C, stirred at 85 rpm for 1 h, heated to 260°C for vacuum reaction for 20 min, naturally cooled to room temperature, and pelletized to obtain modified polyester pellets; modified polyester pellets, modified hollow mesoporous nano-cerium oxide and polyethylene glycol 10000 were mixed in a mass ratio of 1:0.04:0.02 and spun using a twin-screw spinning machine. , nitrogen was introduced as the core liquid, melt spinning was carried out under the conditions of 1500 spinneret holes, 4 cm windless zone height, 1400 m / min, 120 m / min, melt receiving amount 550 kg / h, total stretching ratio of post-spinning 3.7, first stretching ratio 3.27, second stretching ratio 1.08, spinning temperature 289°C, blowing temperature 22°C, blowing humidity 75% RH, cooling and solidification in air, washing with deionized water 5 times, and drying at 30°C for 23 h to obtain spun fibers; (5) The spun fiber was immersed in a 0.3 mol / L pyrrole solution, ultrasonicated for 25 min, and then a 0.5 mol / L ferric chloride solution was added, wherein the molar ratio of ferric chloride to pyrrole was 3:1. After ultrasonicating at 5°C for 55 min, the fiber was taken out, washed with deionized water for 5 times, and dried at 65°C for 8 h to obtain a modified fiber. The modified fiber and wool fiber were mixed at a mass ratio of 1:1, blended on a B412 blending machine, and then combed with the first needle, second needle, fine combing, and third needle combing on a CSN needle combing machine. The yarn was treated by drawing and twisting on a FB441 roving frame, and drawn and twisted on a SHS24 spinning frame to obtain a blended yarn; the blended yarn was woven on a machine with a 2 / 1 right-hand twill weave at a fabric tightness of 97.33% to obtain a treated fabric; the treated fabric and a mixed solution of sodium hypochlorite were mixed at a mass ratio of 1:35, immersed at 30°C for 55min, taken out and washed with deionized water for 5 times, and dried at 50°C for 1h to obtain a warm fabric containing hollow polyester fiber.

[0030] Comparative Example 1: A method for preparing a thermal insulation fabric containing hollow polyester fibers, the method comprising the following preparation steps: (1) Hollow mesoporous nano-cerium oxide, hexadecyltrimethylammonium chloride and deionized water were mixed in a mass ratio of 1:0.025:90, ultrasonicated for 30 minutes, melted paraffin 10 times the mass of the hollow mesoporous nano-cerium oxide was added, stirred at 70°C and 7500rpm for 10 minutes, allowed to stand and cool to room temperature, filtered, washed with anhydrous ethanol and deionized water for 4 times respectively, dried at 55°C for 12 hours, ground and sieved through 250 mesh to obtain semi-protected hollow mesoporous nano-cerium oxide; semi-protected hollow mesoporous nano-cerium oxide, chloromethyltrimethoxysilane and 97.5% ethanol aqueous solution were mixed in a mass ratio of 1:1.8:200, ultrasonically dispersed for 30 minutes, heated to 60°C and stirred at 250rpm for 3 hours, naturally cooled to room temperature and centrifuged, washed with anhydrous ethanol for 4 times, dried at 50°C for 48 hours, and pre-modified hollow mesoporous nano-cerium oxide was obtained; (2) Pre-modified hollow mesoporous nano-cerium oxide, isocyanuric acid, sodium hydroxide and deionized water were mixed in a mass ratio of 1:2.5:1.5:100, stirred at 25°C and 350 rpm for 12 h, and a 55% mass fraction sulfuric acid solution was added to adjust the pH to 6. After standing for 1.5 h, the mixture was filtered and washed with deionized water for 4 times to obtain semi-modified hollow mesoporous nano-cerium oxide. Semi-modified hollow mesoporous nano-cerium oxide and chloroform were mixed in a mass ratio of 1:10, stirred at 25°C and 150 rpm for 90 m in, filtered, washed with chloroform, anhydrous ethanol and deionized water for 4 times, dried at 40°C for 24h, and obtained semi-modified hollow mesoporous nano-cerium oxide; semi-modified hollow mesoporous nano-cerium oxide, N-(3-trimethoxysilylpropyl)pyrrole and anhydrous ethanol were mixed in a mass ratio of 1:0.25:50, stirred at 50°C and 250rpm for 4h, naturally cooled to room temperature and filtered, washed with anhydrous ethanol and deionized water for 4 times, and dried at 40°C for 24h to obtain modified hollow mesoporous nano-cerium oxide; (3) Terephthalic acid, dimethyl chlorophosphate, ethylene glycol and ethylene glycol antimony were mixed in a mass ratio of 1:0.4:0.65:0.02, heated at 145°C for 25 min, heated to 180°C, stirred at 80 rpm for 2 h, heated to 250°C for vacuum reaction for 25 min, cooled naturally to room temperature, and pelletized to obtain modified polyester pellets; the modified polyester pellets, modified hollow mesoporous nano-cerium oxide and polyethylene glycol 10000 were mixed in a mass ratio of 1:0.03:0.015, and spun by a twin-screw spinning machine. A spinning machine was used, nitrogen was introduced as the core liquid, and melt spinning was performed under the conditions of 1400 spinneret holes, 3 cm windless zone height, 1300 m / min, 115 m / min, melt receiving amount, 500 kg / h, total stretching ratio of 3.6, first stretching ratio, 3.26, second stretching ratio, 1.07, spinning temperature, 288°C, blowing temperature, 21°C, and blowing humidity, 70% RH, and the fibers were cooled and solidified in the air, washed with deionized water for 4 times, and dried at 25°C for 24 hours to obtain spun fibers; (4) The spun fiber was immersed in a 0.2 mol / L pyrrole solution, ultrasonicated for 20 min, and then a 0.4 mol / L ferric chloride solution was added, wherein the molar ratio of ferric chloride to pyrrole was 3:1. After ultrasonication at 2.5°C for 60 min, the fiber was taken out, washed with deionized water for 4 times, and dried at 60°C for 9 h to obtain a modified fiber. The modified fiber and wool fiber were mixed at a mass ratio of 1:1, blended on a B412 blending machine, and then combed on a CSN needle combing machine using the first needle, second needle, combing, and third needle. The yarn was carded, stretched and twisted on a FB441 roving frame, stretched and twisted on a SHS24 spinning frame to obtain a blended yarn; the blended yarn was woven on a machine with a 2 / 1 right-hand twill weave at a fabric tightness of 97.33% to obtain a treated fabric; the treated fabric and a sodium hypochlorite mixture were mixed at a mass ratio of 1:30, immersed at 25°C for 60 minutes, taken out and washed with deionized water for 4 times, and dried at 45°C for 2 hours to obtain a warm fabric containing hollow polyester fibers.

[0031] Comparative Example 2: A method for preparing a thermal insulation fabric containing hollow polyester fibers, the method comprising the following preparation steps: (1) Hollow mesoporous nano-cerium oxide, hexadecyltrimethylammonium chloride and deionized water were mixed in a mass ratio of 1:0.025:90, ultrasonicated for 30 minutes, melted paraffin 10 times the mass of the hollow mesoporous nano-cerium oxide was added, stirred at 70°C and 7500rpm for 10 minutes, allowed to stand and cool to room temperature, filtered, washed with anhydrous ethanol and deionized water for 4 times respectively, dried at 55°C for 12 hours, ground and sieved through 250 mesh to obtain semi-protected hollow mesoporous nano-cerium oxide; semi-protected hollow mesoporous nano-cerium oxide, chloromethyltrimethoxysilane and 97.5% ethanol aqueous solution were mixed in a mass ratio of 1:1.8:200, ultrasonically dispersed for 30 minutes, heated to 60°C and stirred at 250rpm for 3 hours, naturally cooled to room temperature and centrifuged, washed with anhydrous ethanol for 4 times, dried at 50°C for 48 hours, and pre-modified hollow mesoporous nano-cerium oxide was obtained; (2) Pre-modified hollow mesoporous nano-cerium oxide, isocyanuric acid, sodium hydroxide and deionized water were mixed in a mass ratio of 1:2.5:1.5:100, stirred at 25°C and 350 rpm for 12 h, and a 55% mass fraction sulfuric acid solution was added to adjust the pH to 6. After standing for 1.5 h, the mixture was filtered and washed with deionized water for 4 times to obtain semi-modified hollow mesoporous nano-cerium oxide. Semi-modified hollow mesoporous nano-cerium oxide and chloroform were mixed in a mass ratio of 1:10, stirred at 25°C and 150 rpm for 90 m in, filtered, washed with chloroform, anhydrous ethanol and deionized water for 4 times, dried at 40°C for 24h, and obtained semi-modified hollow mesoporous nano-cerium oxide; semi-modified hollow mesoporous nano-cerium oxide, N-(3-trimethoxysilylpropyl)pyrrole and anhydrous ethanol were mixed in a mass ratio of 1:0.25:50, stirred at 50°C and 250rpm for 4h, naturally cooled to room temperature and filtered, washed with anhydrous ethanol and deionized water for 4 times, and dried at 40°C for 24h to obtain modified hollow mesoporous nano-cerium oxide; (3) Terephthalic acid, ethylene glycol and ethylene glycol antimony were mixed in a mass ratio of 1:0.55:0.02, heated at 145°C for 25 min, heated to 180°C, stirred at 80 rpm for 2 h, heated to 250°C for vacuum reaction for 25 min, naturally cooled to room temperature, and pelletized to obtain polyester pellets; polyester pellets, modified hollow mesoporous nano-cerium oxide and polyethylene glycol 10000 were mixed in a mass ratio of 1:0.03:0.015, and nitrogen was introduced into a twin-screw spinning machine. The core liquid was melt-spinned under the conditions of 1400 spinneret holes, 3 cm windless zone height, 1300 m / min, 115 m / min spinning speed, 500 kg / h melt receiving amount, 3.6 total stretching ratio after spinning, 3.26 first stretching ratio, 1.07 second stretching ratio, 288°C spinning temperature, 21°C blowing temperature, 70% RH blowing humidity, cooled and solidified in air, washed 4 times with deionized water, and dried at 25°C for 24 h to obtain spun fibers; (4) The spun fiber was immersed in a 0.2 mol / L pyrrole solution, ultrasonicated for 20 min, and then a 0.4 mol / L ferric chloride solution was added, wherein the molar ratio of ferric chloride to pyrrole was 3:1. After ultrasonication at 2.5°C for 60 min, the fiber was taken out, washed with deionized water for 4 times, and dried at 60°C for 9 h to obtain a modified fiber. The modified fiber and wool fiber were mixed at a mass ratio of 1:1, blended on a B412 blending machine, and then combed on a CSN needle combing machine using the first needle, second needle, combing, and third needle. The yarn was carded, stretched and twisted on a FB441 roving frame, stretched and twisted on a SHS24 spinning frame to obtain a blended yarn; the blended yarn was woven on a machine with a 2 / 1 right-hand twill weave at a fabric tightness of 97.33% to obtain a treated fabric; the treated fabric and a sodium hypochlorite mixture were mixed at a mass ratio of 1:30, immersed at 25°C for 60 minutes, taken out and washed with deionized water for 4 times, and dried at 45°C for 2 hours to obtain a warm fabric containing hollow polyester fibers.

[0032] Comparative Example 3: A method for preparing a thermal insulation fabric containing hollow polyester fibers, the method comprising the following preparation steps: (1) Hollow mesoporous nano-cerium oxide, hexadecyltrimethylammonium chloride and deionized water were mixed in a mass ratio of 1:0.025:90, ultrasonicated for 30 minutes, melted paraffin 10 times the mass of the hollow mesoporous nano-cerium oxide was added, stirred at 70°C and 7500rpm for 10 minutes, allowed to stand and cool to room temperature, filtered, washed with anhydrous ethanol and deionized water for 4 times respectively, dried at 55°C for 12 hours, ground and sieved through 250 mesh to obtain semi-protected hollow mesoporous nano-cerium oxide; semi-protected hollow mesoporous nano-cerium oxide, chloromethyltrimethoxysilane and 97.5% ethanol aqueous solution were mixed in a mass ratio of 1:1.8:200, ultrasonically dispersed for 30 minutes, heated to 60°C and stirred at 250rpm for 3 hours, naturally cooled to room temperature and centrifuged, washed with anhydrous ethanol for 4 times, dried at 50°C for 48 hours, and pre-modified hollow mesoporous nano-cerium oxide was obtained; (2) The pre-modified hollow mesoporous nano-cerium oxide, isocyanuric acid, sodium hydroxide and deionized water were mixed in a mass ratio of 1:2.5:1.5:100, stirred at 25°C and 350 rpm for 12 h, and a 55% mass fraction sulfuric acid solution was added to adjust the pH to 6. After standing for 1.5 h, the mixture was filtered and washed with deionized water for 4 times to obtain semi-modified hollow mesoporous nano-cerium oxide; the semi-modified hollow mesoporous nano-cerium oxide and chloroform were mixed in a mass ratio of 1:10, stirred at 25°C and 150 rpm for 90 min, filtered, washed with chloroform, anhydrous ethanol and deionized water for 4 times respectively, and dried at 40°C for 24 h to obtain semi-modified hollow mesoporous nano-cerium oxide; (3) 5-(1H-pyrrol-1-yl)-2-mercaptobenzimidazole, triethylamine and tetrahydrofuran were mixed in a mass ratio of 1:0.6:11, stirred at 300 rpm for 15 min in a nitrogen atmosphere, and dimethyl chlorophosphate (0.65 times the mass of 5-(1H-pyrrol-1-yl)-2-mercaptobenzimidazole) was added dropwise at 2.5°C. The temperature was raised to 50°C and stirred for 6 h. Ethyl acetate was added for extraction. The organic phase was dried over anhydrous sodium sulfate and filtered, rotary evaporated, and separated and purified with petroleum ether ethyl acetate eluent to obtain a multifunctional monomer. (4) Terephthalic acid, multifunctional monomer, ethylene glycol and ethylene glycol antimony were mixed in a mass ratio of 1:0.85:0.65:0.02, heated at 145°C for 25 min, heated to 180°C, stirred at 80 rpm for 2 h, heated to 250°C for vacuum reaction for 25 min, cooled naturally to room temperature, and pelletized to obtain modified polyester pellets; modified polyester pellets, semi-modified hollow mesoporous nano-cerium oxide and polyethylene glycol 10000 were mixed in a mass ratio of 1:0.03:0.015, and spun by a twin-screw spinning machine. A spinning machine was used, nitrogen was introduced as the core liquid, and melt spinning was performed under the conditions of 1400 spinneret holes, 3 cm windless zone height, 1300 m / min, 115 m / min, melt receiving amount, 500 kg / h, total stretching ratio of 3.6, first stretching ratio, 3.26, second stretching ratio, 1.07, spinning temperature, 288°C, blowing temperature, 21°C, and blowing humidity, 70% RH, and the fibers were cooled and solidified in the air, washed with deionized water for 4 times, and dried at 25°C for 24 hours to obtain spun fibers; (5) The spun fiber was immersed in a 0.2 mol / L pyrrole solution, ultrasonicated for 20 min, and then a 0.4 mol / L ferric chloride solution was added, wherein the molar ratio of ferric chloride to pyrrole was 3:1. After ultrasonicating at 2.5°C for 60 min, the fiber was taken out, washed with deionized water for 4 times, and dried at 60°C for 9 h to obtain a modified fiber. The modified fiber and wool fiber were mixed at a mass ratio of 1:1, blended on a B412 blending machine, and then combed on a CSN needle combing machine using the first needle, second needle, combing, and third needle. The yarn was carded, stretched and twisted on a FB441 roving frame, stretched and twisted on a SHS24 spinning frame to obtain a blended yarn; the blended yarn was woven on a machine with a 2 / 1 right-hand twill weave at a fabric tightness of 97.33% to obtain a treated fabric; the treated fabric and a sodium hypochlorite mixture were mixed at a mass ratio of 1:30, immersed at 25°C for 60 minutes, taken out and washed with deionized water for 4 times, and dried at 45°C for 2 hours to obtain a warm fabric containing hollow polyester fibers.

[0033] Comparative Example 4: A method for preparing a thermal insulation fabric containing hollow polyester fibers, the method comprising the following preparation steps: (1) Hollow mesoporous nano-cerium oxide, hexadecyltrimethylammonium chloride and deionized water were mixed in a mass ratio of 1:0.025:90, ultrasonicated for 30 minutes, melted paraffin 10 times the mass of the hollow mesoporous nano-cerium oxide was added, stirred at 70°C and 7500rpm for 10 minutes, allowed to stand and cool to room temperature, filtered, washed with anhydrous ethanol and deionized water for 4 times respectively, dried at 55°C for 12 hours, ground and sieved through 250 mesh to obtain semi-protected hollow mesoporous nano-cerium oxide; semi-protected hollow mesoporous nano-cerium oxide, chloromethyltrimethoxysilane and 97.5% ethanol aqueous solution were mixed in a mass ratio of 1:1.8:200, ultrasonically dispersed for 30 minutes, heated to 60°C and stirred at 250rpm for 3 hours, naturally cooled to room temperature and centrifuged, washed with anhydrous ethanol for 4 times, dried at 50°C for 48 hours, and pre-modified hollow mesoporous nano-cerium oxide was obtained; (2) The pre-modified hollow mesoporous nano-cerium oxide and chloroform were mixed in a mass ratio of 1:10, stirred at 25°C and 150 rpm for 90 min, filtered, washed with chloroform, anhydrous ethanol and deionized water for 4 times, dried at 40°C for 24 h, and obtained the separated pre-modified hollow mesoporous nano-cerium oxide; the separated pre-modified hollow mesoporous nano-cerium oxide, N-(3-trimethoxysilylpropyl)pyrrole and anhydrous ethanol were mixed in a mass ratio of 1:0.25:50, stirred at 50°C and 250 rpm for 4 h, naturally cooled to room temperature and filtered, washed with anhydrous ethanol and deionized water for 4 times, dried at 40°C for 24 h, and obtained the modified hollow mesoporous nano-cerium oxide; (3) 5-(1H-pyrrol-1-yl)-2-mercaptobenzimidazole, triethylamine and tetrahydrofuran were mixed in a mass ratio of 1:0.6:11, stirred at 300 rpm for 15 min in a nitrogen atmosphere, and dimethyl chlorophosphate (0.65 times the mass of 5-(1H-pyrrol-1-yl)-2-mercaptobenzimidazole) was added dropwise at 2.5°C. The temperature was raised to 50°C and stirred for 6 h. Ethyl acetate was added for extraction. The organic phase was dried over anhydrous sodium sulfate and filtered, rotary evaporated, and separated and purified with petroleum ether ethyl acetate eluent to obtain a multifunctional monomer. (4) Terephthalic acid, multifunctional monomer, ethylene glycol and ethylene glycol antimony were mixed in a mass ratio of 1:0.85:0.65:0.02, heated at 145°C for 25 min, heated to 180°C, stirred at 80 rpm for 2 h, heated to 250°C for vacuum reaction for 25 min, cooled naturally to room temperature, and pelletized to obtain modified polyester pellets; modified polyester pellets, modified hollow mesoporous nano-cerium oxide and polyethylene glycol 10000 were mixed in a mass ratio of 1:0.03:0.015, and spun by a twin-screw spinning machine. A spinning machine was used, nitrogen was introduced as the core liquid, and melt spinning was performed under the conditions of 1400 spinneret holes, 3 cm windless zone height, 1300 m / min, 115 m / min, melt receiving amount, 500 kg / h, total stretching ratio of 3.6, first stretching ratio, 3.26, second stretching ratio, 1.07, spinning temperature, 288°C, blowing temperature, 21°C, and blowing humidity, 70% RH, and the fibers were cooled and solidified in the air, washed with deionized water for 4 times, and dried at 25°C for 24 hours to obtain spun fibers; (5) The spun fiber was immersed in a 0.2 mol / L pyrrole solution, ultrasonicated for 20 min, and then a 0.4 mol / L ferric chloride solution was added, wherein the molar ratio of ferric chloride to pyrrole was 3:1. After ultrasonicating at 2.5°C for 60 min, the fiber was taken out, washed with deionized water for 4 times, and dried at 60°C for 9 h to obtain a modified fiber. The modified fiber and wool fiber were mixed at a mass ratio of 1:1, blended on a B412 blending machine, and then combed on a CSN needle combing machine using the first needle, second needle, combing, and third needle. The yarn was carded, stretched and twisted on a FB441 roving frame, stretched and twisted on a SHS24 spinning frame to obtain a blended yarn; the blended yarn was woven on a machine with a 2 / 1 right-hand twill weave at a fabric tightness of 97.33% to obtain a treated fabric; the treated fabric and a sodium hypochlorite mixture were mixed at a mass ratio of 1:30, immersed at 25°C for 60 minutes, taken out and washed with deionized water for 4 times, and dried at 45°C for 2 hours to obtain a warm fabric containing hollow polyester fibers.

[0034] Test Example 1: 1. Warmth Test method: The thermal insulation fabrics containing hollow polyester fibers obtained in each example and the comparative example were tested according to GB / T11048, and 35×35 cm 2 The heat transfer coefficient of samples of different sizes is tested using a flat plate heat preservation instrument model YG606L.

[0035] 2. Antibacterial Test method: Cut the warm-keeping fabrics containing hollow polyester fibers obtained in each embodiment and the comparative example into samples of 2.54 cm × 2.54 cm in size, drip 25 μL of 2.00 × 10 7coli liquid containing CFU, take another identical sample and cover it on the sample inoculated with bacteria, add sterile weights and let it stand for 10 minutes (no sample is the blank group), put it into 5mL of sterile sodium thiosulfate solution with a concentration of 0.01mol / L, ultrasonicate for 30min and then centrifuge, dilute the same multiple with 0.01mol / L hydrochloric acid solution, incubate at 37℃ for 24h and then count, calculate the inhibition rate = (blank solution bacteria count - sample solution bacteria count) / blank solution bacteria count * 100%.

[0036] 3. Flame retardancy Test method: The thermal insulation fabrics containing hollow polyester fibers obtained in each example and the comparative example were tested for limiting oxygen index using an FTA limiting oxygen index instrument according to GB / T5454.

[0037] Table 1 below shows the analysis results of the thermal insulation, antibacterial and flame retardant properties of the thermal insulation fabrics containing hollow polyester fibers according to Examples 1 to 3 of the present invention and Comparative Examples 1 to 4.

[0038]

[0039] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 4 in Table 1, it can be found that the thermal insulation fabric containing hollow polyester fibers prepared in the present invention has good thermal insulation, antibacterial and flame retardant properties.

[0040] By comparison, the heat transfer coefficients of Examples 1, 2, 3 and Comparative Examples 1, 2, 3 and 4 are almost the same, indicating that the use of hollow mesoporous nano-cerium oxide as a reinforcing phase and the hollow structure can effectively reduce heat conduction and improve the warmth retention of thermal fabrics containing hollow polyester fibers; wool fibers are selected for blending with hollow polyester fibers, and the curled shape of the wool fibers forms many tiny gaps that can store a large amount of air, thereby effectively blocking the invasion of external cold air and further improving the warmth retention of thermal fabrics containing hollow polyester fibers.

[0041] By comparison, the limiting oxygen index of Examples 1, 2, and 3 is higher than that of Comparative Example 2, which indicates that a multifunctional monomer with phosphorus and a benzene ring conjugated group is synthesized by substitution reaction of mercapto and acyl chloride to participate in the polymerization of the polyester main chain. The phosphorus element can inhibit the generation of free radicals and promote the formation of a carbonized protective layer during the propagation of flames, thereby slowing down the rate of the combustion reaction and improving the flame retardant properties of the thermal insulation fabric containing hollow polyester fibers.

[0042] By comparison, the antibacterial rates of Examples 1, 2, and 3 are higher than those of Comparative Example 4, which shows that paraffin is used as the oil phase to selectively protect the hollow mesoporous nano-cerium oxide, and isocyanuric acid is grafted on the surface of the hollow mesoporous nano-cerium oxide to form a halamine precursor, which reacts with sodium hypochlorite to obtain a halamine structure that can destroy or prevent the normal metabolism of cells and promote the death of bacteria, thereby improving the antibacterial properties of the thermal insulation fabric containing the hollow polyester fiber.

[0043] Test Example 2: 1. Antistatic Test method: The thermal insulation fabrics containing hollow polyester fibers obtained in each embodiment and the comparative example were tested for static voltage half-life according to GB / T12703.

[0044] 2. Mechanical properties Test method: The thermal insulation fabrics containing hollow polyester fibers obtained in each embodiment and the comparative example are cut into strips with a length of 20 cm and a width of 6 cm according to GB / T3923, and the burrs of the yarns on both sides of the width direction are removed in equal numbers. The breaking strength N0 is tested under the conditions of a clamping distance of 100 mm and a tensile speed of 100 mm / min.

[0045] 3. Anti-aging Test method: The thermal insulation fabrics containing hollow polyester fibers obtained in each embodiment and the comparative example were placed in the UV irradiation room of an aging machine, and the UV light wavelength was 315-400nm and the power was 0.89W / m 3 , the test temperature is set to 60℃, and ultraviolet light irradiation is carried out for 24 hours. The breaking strength N1 is measured again according to GB / T3923, and the aging rate is calculated as (N0-N1) / N0*100%.

[0046] Table 2 below shows the analysis results of the anti-aging, antistatic and mechanical properties of the thermal insulation fabrics containing hollow polyester fibers according to Examples 1 to 3 of the present invention and Comparative Examples 1 to 4.

[0047]

[0048] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 4 in Table 4, it can be found that the thermal insulation fabric containing hollow polyester fibers prepared in the present invention has good anti-aging, antistatic and mechanical properties.

[0049] By comparison, compared with Example 1, Examples 1, 2, and 3, the electrostatic voltage half-life and aging rate are lower and the breaking strength is higher, which illustrates that a multifunctional monomer with a phosphorus element and a benzene ring conjugated group is synthesized by substitution reaction between mercapto and acyl chloride to participate in the polymerization of the polyester main chain, and the conjugated ring in 5-(1H-pyrrole-1-yl)-2-mercaptobenzimidazole can absorb ultraviolet rays, thereby improving the anti-aging properties of the thermal insulation fabric containing the hollow polyester fiber; polyethylene glycol 10000 is used as a porogen to facilitate the polymerization of pyrrole between the modified polyester pellets and the modified hollow mesoporous nano-cerium oxide to form a long chain, thereby constructing a cross-linked network, thereby further improving the mechanical properties and antistatic properties of the thermal insulation fabric containing the hollow polyester fiber.

[0050] By comparison, Examples 1, 2, and 3 have lower electrostatic voltage half-life and higher breaking strength than Comparative Example 3, indicating that N-(3-trimethoxysilylpropyl)pyrrole is grafted on the other surface of the hollow mesoporous nano-cerium oxide to form a polypyrrole long chain with the polyester main chain, thereby improving the mechanical properties of the thermal insulation fabric containing the hollow polyester fiber. At the same time, the conjugated chain structure of the polypyrrole long chain has good electron transmission ability, further improving the antistatic property of the thermal insulation fabric containing the hollow polyester fiber.

[0051] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A thermal insulation fabric containing hollow polyester fibers, characterized in that: The thermal insulation fabric containing hollow polyester fiber is prepared by mixing modified polyester pellets, modified hollow mesoporous nano cerium oxide and polyethylene glycol 10000, then melt spinning, treating with pyrrole solution, twisting spinning and weaving, and then treating with sodium hypochlorite mixed solution; the modified polyester pellets are obtained by reacting 5-(1H-pyrrole-1-yl)-2-mercaptobenzimidazole with dimethyl chlorophosphate, and then reacting with terephthalic acid and ethylene glycol; the modified hollow mesoporous nano cerium oxide is obtained by selectively protecting the hollow mesoporous nano cerium oxide with melted paraffin, reacting with chloromethyltrimethoxysilane and isocyanuric acid in sequence, dissolving the paraffin with chloroform, and then grafting N-(3-trimethoxysilylpropyl) pyrrole.

2. A method for preparing a thermal insulation fabric containing hollow polyester fibers, characterized in that: The method comprises the following preparation steps: (1) Mixing hollow mesoporous nano-cerium oxide, hexadecyltrimethylammonium chloride and deionized water, adding melted paraffin after ultrasonic treatment, stirring at 65-75°C, filtering, washing, drying, grinding and sieving to obtain semi-protected hollow mesoporous nano-cerium oxide; mixing semi-protected hollow mesoporous nano-cerium oxide, chloromethyltrimethoxysilane and ethanol aqueous solution, ultrasonically dispersing, stirring at 55-65°C for 2-4h, cooling to room temperature and centrifuging, washing and drying to obtain pre-modified hollow mesoporous nano-cerium oxide; (2) Pre-modified hollow mesoporous nano-cerium oxide, isocyanuric acid, sodium hydroxide and deionized water are mixed in a mass ratio of 1: (2-3): (1-2): (90-110), stirred at 20-30°C for 11-13 hours, sulfuric acid solution is added to adjust the pH to 5-7, and the mixture is allowed to stand for 1-2 hours before filtering, washing and drying to obtain semi-modified hollow mesoporous nano-cerium oxide; semi-modified hollow mesoporous nano-cerium oxide, N-(3-trimethoxysilylpropyl) pyrrole and anhydrous ethanol are mixed in a mass ratio of 1: (0.2-0.3): (45-55), stirred at 45-55°C for 3-5 hours, cooled to room temperature before filtering, washing and drying to obtain modified hollow mesoporous nano-cerium oxide; (3) 5-(1H-pyrrol-1-yl)-2-mercaptobenzimidazole, triethylamine and tetrahydrofuran were mixed in a mass ratio of 1: (0.5-0.7): (10-12), and dimethyl chlorophosphate (0.6-0.7 times the mass of 5-(1H-pyrrol-1-yl)-2-mercaptobenzimidazole) was added dropwise at 0-5°C in a nitrogen atmosphere, and the temperature was raised to 45-55°C and stirred for 5-7h. Ethyl acetate was added for extraction, and the organic phase was dried over anhydrous sodium sulfate and filtered, rotary evaporated, and separated and purified with petroleum ether ethyl acetate eluent to obtain a multifunctional monomer; (4) mixing terephthalic acid, multifunctional monomer, ethylene glycol and ethylene glycol antimony in a mass ratio of 1: (0.8-0.9): (0.6-0.7): (0.01-0.03), heating at 140-150°C for 20-30 min, heating to 175-185°C and stirring for 1-3 h, heating to 240-260°C and reacting in vacuum for 20-30 min, cooling to room temperature, taking out pellets to obtain modified polyester pellets; mixing the modified polyester pellets, modified hollow mesoporous nano-cerium oxide and polyethylene glycol 10000 in a mass ratio of 1: (0.02-0.04): (0.01-0.02), using a twin-screw spinning machine, introducing nitrogen as the core liquid, performing melt spinning, cooling and solidifying in air, washing and drying, and obtaining spun fibers; (5) Immerse the spun fiber in a 0.1-0.3 mol / L pyrrole solution, disperse it ultrasonically, add a 0.3-0.5 mol / L ferric chloride solution, wherein the molar ratio of ferric chloride to pyrrole is 3:1, ultrasonicate at 0-5°C for 55-65 min, take it out, wash and dry it to obtain a modified fiber; use a 2 / 1 right-hand twill weave on a machine at a fabric tightness of 97.33% to obtain a fabric to be treated; mix the fabric to be treated and a sodium hypochlorite mixture at a mass ratio of 1:(25-35), immerse it at 20-30°C for 55-65 min, take it out, wash and dry it, and obtain a thermal insulation fabric containing hollow polyester fibers.

3. The method for preparing a thermal insulation fabric containing hollow polyester fibers according to claim 2, characterized in that: The semi-protected hollow mesoporous nano-cerium oxide in step (1) is prepared by mixing the hollow mesoporous nano-cerium oxide, hexadecyltrimethylammonium chloride and deionized water in a mass ratio of 1: (0.02-0.03): (85-95), ultrasonicating for 25-35 minutes, adding 9-11 times the mass of the hollow mesoporous nano-cerium oxide and melted paraffin heated at 70°C, stirring at 65-75°C and 7000-8000 rpm for 5-15 minutes, standing and cooling to room temperature, filtering, washing with anhydrous ethanol and deionized water for 3-5 times respectively, drying at 50-60°C for 11-13 hours, and grinding and sieving 200-300 mesh to obtain the obtained product.

4. The method for preparing a thermal insulation fabric containing hollow polyester fibers according to claim 2, characterized in that: The pre-modified hollow mesoporous nano-cerium oxide in step (1) is prepared by mixing semi-protected hollow mesoporous nano-cerium oxide, chloromethyltrimethoxysilane and 97% to 98% ethanol aqueous solution in a mass ratio of 1: (1.7 to 1.9): (150 to 250), ultrasonically dispersing for 25 to 35 minutes, stirring at 55 to 65° C. and 200 to 300 rpm for 2 to 4 hours, naturally cooling to room temperature and then centrifuging, washing with anhydrous ethanol for 3 to 5 times, and drying at 45 to 55° C. for 47 to 49 hours.

5. The method for preparing a thermal insulation fabric containing hollow polyester fibers according to claim 2, characterized in that: The semi-modified hollow mesoporous nano-cerium oxide in step (2) is obtained by mixing the semi-modified hollow mesoporous nano-cerium oxide and chloroform in a mass ratio of 1:(9-11), stirring at 20-30° C. for 85-95 min, filtering, washing and drying.

6. The method for preparing a thermal insulation fabric containing hollow polyester fibers according to claim 2, characterized in that: The process parameters of the melt spinning in step (4) are as follows: spinneret hole number 1300~1500 holes, windless zone height 2~4 cm, spinning speed 1200~1400 m / min, 110~120 m / min, melt receiving amount 450~550 kg / h, post-spinning total stretching ratio 3.5~3.7, first stretching ratio 3.25~3.27, second stretching ratio 1.06~1.08, spinning temperature 287~289°C, blowing temperature 20~22°C, and blowing humidity 65%~75% RH.

7. The method for preparing a thermal insulation fabric containing hollow polyester fibers according to claim 2, characterized in that: The blended yarn in step (5) is obtained by mixing the modified fiber and the wool fiber in a mass ratio of 1:1, blending on a B412 blending machine, and then combing with the first needle, second needle, fine combing, and third needle on a CSN gill combing machine, drawing and twisting on a FB441 roving frame, and drawing and twisting on a SHS24 spinning frame.

8. The method for preparing a thermal insulation fabric containing hollow polyester fibers according to claim 7, characterized in that: The parameters of the blended yarn are: single yarn count 73 / 1, twist 780 twists / m, twist direction Z; ply yarn 72 / 2, twist 800 twists / m, twist direction S.

9. The method for preparing a thermal insulation fabric containing hollow polyester fibers according to claim 2, characterized in that: The sodium hypochlorite mixed solution in step (5) is obtained by mixing sodium hypochlorite solution and deionized water in a volume ratio of 1:10, and adding 60% by mass sulfuric acid solution to adjust the pH to 7.

10. Use of the thermal insulation fabric containing hollow polyester fibers according to claim 1 in textiles.

Citation Information

Cited By

  • Antistatic modified polyamide fiber and preparation method thereof

    CN120174504A

  • Special-shaped section rare earth modified polyester / bamboo fiber blended medical yarn and preparation method thereof

    CN120537059A

  • Waterproof antifouling fabric and preparation method thereof

    CN121204853A